A method for measuring the molecular ratio of inhalation to exhalation and effect of inspired oxygen levels on oxygen consumption - Koichiro Shinozaki (Nature Portfolio, 2021)
Abstract Using a new method for measuring the molecular ratio (R) of inhalation to exhalation, we investigated the effect of high fraction of inspired oxygen (FIO2) on oxygen consumption (VO2), carbon dioxide generation (VCO2), and respiratory quotient (RQ) in mechanically ventilated rats. Twelve rats were equally assigned into two groups by anesthetics: intravenous midazolam/fentanyl vs. inhaled isoflurane. R, VO2, VCO2, and RQ were measured at FIO2 0.3 or 1.0. R error was ± 0.003. R was 1.0099 ± 0.0023 with isoflurane and 1.0074 ± 0.0018 with midazolam/fentanyl. R was 1.0081 ± 0.0017 at an FIO2 of 0.3 and 1.0092 ± 0.0029 at an FIO2 of 1.0. There were no differences in VCO2 among the groups. VO2 increased at FIO2 1.0, which was more notable when midazolam/fentanyl was used (isoflurane-FIO2 0.3: 15.4 ± 1.1; isoflurane-FIO2 1.0: 17.2 ± 1.8; midazolam/fentanyl-FIO2 0.3: 15.4 ± 1.1; midazolam/fentanyl-FIO2 1.0: 21.0 ± 2.2 mL/kg/min at STP). The RQ was lower at FIO2 1.0 than FIO2 0.3 (isoflurane-FIO2 0.3: 0.80 ± 0.07; isoflurane-FIO2 1.0: 0.71 ± 0.05; midazolam/fentanyl-FIO2 0.3: 0.79 ± 0.03; midazolam/fentanyl-FIO2 1.0: 0.59 ± 0.04). R was not affected by either anesthetics or FIO2. Inspired 100% O2 increased VO2 and decreased RQ, which might be more remarkable when midazolam/fentanyl was used.